What type of cell death occurs in chronic cerebral hypoperfusion? A review focusing on pyroptosis and its potential therapeutic implications - He, Yuxuan; Chen, Xi; Wu, Min; Hou, Xianhua; Zhou, Zhenhua (Frontiers in Cellular Neuroscience, 2023)
Chronic cerebral hypoperfusion (CCH) is a major global disease with chronic cerebral blood flow reduction. It is also the main cause of cognitive impairment and neurodegenerative diseases. Pyroptosis, a novel form of cell death, is characterized by the rupture of the cell membrane and the release of pro-inflammatory mediators. In recent years, an increasing number of studies have identified the involvement of pyroptosis and its mediated inflammatory response in the pathological process of CCH. Therefore, preventing the activation of pyroptosis following CCH is beneficial to inhibit the inflammatory cascade and reduce brain injury. In this review, we discuss the research progress on the relationship between pyroptosis and CCH, in order to provide a reference for research in related fields.